Pendekatan Humanistik Dalam Pembelajaran IPS: Memanusiakan Siswa Dalam Proses Pendidikan - Fanisa Putri Anggraini; Viora Selamata; Arif Rizky; Sani Safitri (FKIP, Universitas Palangka Raya, 2025)
The humanistic approach in social studies learning emphasizes holistic student development, including cognitive, emotional and social aspects. This article aims to examine the application of this approach in social studies learning as well as its benefits and challenges. The method used is a literature study by analyzing various relevant academic sources. The results show that the humanistic approach is able to increase learning motivation, student engagement, and critical thinking skills, helping students understand social issues more deeply and fostering empathy. The teacher acts as a facilitator who creates a learning environment that supports students' exploration and freedom of thought. However, the implementation of this approach faces several challenges, such as limited teacher understanding, limited time in the curriculum, and difficulties in evaluating learning outcomes that are more oriented towards affective and social aspects. Therefore, effective implementation strategies are needed, such as teacher training, project-based learning approaches and integration of humanistic values in the curriculum. With the right strategy, this approach can create a more meaningful and relevant learning experience for students and help them develop independent, critical and caring characters for their social environment